Trends in men's earnings volatility what does the panel study of income dynamics show? - Shin, Donggyun; Solon, Gary 1954- (Working paper series / National Bureau of Economic Research, 2008)
"Using Panel Study of Income Dynamics data for 1969 through 2004, we examine movements in men's earnings volatility. Like many previous studies, we find that earnings volatility is substantially countercyclical. As for secular trends, we find that men's earnings volatility increased during the 1970s, but did not show a clear trend afterwards until a new upward trend appeared in the last few years. These patterns are broadly consistent with the findings of recent studies based on other data sets"--National Bureau of Economic Research web site